PERANCANGAN SISTEM INFORMASI PENDAFTARAN PASIEN RAWAT JALAN MENGGUNAKAN MICROSOFT VISUAL STUDIO 2010 DI PUSKESMAS CIJAGRA LAMA KOTA BANDUNG - Fatwa Annisa Cahya Salsabila; Ceria Febiana; Anita Putri Wijayanti (POLITEKNIK PIKSI GANESHA, 2021)
This study aims to determine the design of an outpatient registration information system using Microsoft Visual Studio 2010 at the Cijagra Lama Public Health Center, Bandung City. The research method used is a qualitative approach supported by data collection techniques by means of observation, interviews, literature studies and internet studies. The development method used is the waterfall method which is assisted by the design of Data Flow Diagrams. This system is made on a desktop basis that uses Microsoft Visual Studio 2010 as a programming language and uses the Microsoft Office Access 2013 database. The problem that often occurs is the length of registration is closely related to the service process because the registration system is often problematic so that it hampers the registration process. design. ( 2 ) Integration of health information systems in order to obtain efficient and effective performance. (3) consider and redevelop the information system for each medical record data processing activity. Keywords: System Design, Information Systems, Registration, Outpatient